Fermi-level equilibrium-driven trap filling in multibandgap PbS quantum dot solids enabling record voltage generation and improved carrier transport in high-performance solar cells - Dambhare, Neha V.; Biswas, Arindam; Sharma, Anjali; Shinde, Dipak Dattatray; Mitra, Anurag; Girade, Vrushali S.; Rath, Arup Kumar (ACS Energy Letters, 2025)
To leverage the unique optical properties of quantum dots (QDs) in solar cells, it is crucial to address electronic traps from unsaturated surface states of high surface area QDs. Despite advancements in surface passivation, even the best-coupled QD solids exhibit significant sub-bandgap trap states. This study introduces engineered multibandgap PbS QD solids that achieve passivation of deep traps below the conduction band through electron migration from dopant QDs. Our findings indicate that electron flow, driven by Fermi energy balancing in blend films, fills deep trap states, reducing trap density by half and shifting trap energy positions closer to the conduction band. During electrical transport, trap filling minimizes trapping and detrapping events, enhancing overall carrier mobility, despite higher-bandgap dopant QDs not contributing to carrier transport due to their unfavorable energy positions. Improved trap passivation in coupled QD solids leads to a record V oc of 725 +/- 10 meV for the 1.33 eV excitonic peak of QDs and a power conversion efficiency exceeding 14% in solar cells.